PESANTREN PENGKADERAN: PENANAMAN NILAI KARAKTER RELIGIUS-NASIONALIS DI PONDOK PESANTREN MUHAMMADIYAH AL-MUNAWAROH KOTA MALANG JAWA TIMUR - Wafi, In’amul; Setyaningsih, Emi; Mustapa, Arif; Rahman, Khalid; Rahmawan, Triya Indra (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This dissemination activity aims to instill and improve the religious-nationalist character of senior students and teachers at the Muhammadiyah Al-Munawaroh Islamic boarding school to maintain harmony between religious communities and with internal religious communities. Strengthening religious-nationalist values ​​provided training methods consisting of socialization, problem identification, socio-economic and cultural mapping of society to senior students and teachers. The techniques used include conducting surveys, focus group discussions, and designing training projects. The results of this dissemination activity show that it is working effectively to develop the capacity of students and teachers, as well as providing improvements in Islamic boarding school management, curriculum design and roles in society. Santri and teachers from various regions in Indonesia are given the knowledge and skills needed to become pioneering preaching cadres of religious-nationalist character in society.